ANALISIS METODE PLS-SEM DENGAN MODIFIKASI MODEL UTAUT2 PADA PENGGUNAAN CHATGPT OLEH MAHASISWA UNIVERSITAS SUMATERA UTARA - Silalahi, Putri Mayang Syafira; br Tarigan, Enita Dewi; Pane, Rahmawati; Suyanto, Suyanto (Universitas Islam Sumatera Utara, 2024)
The rapid advancement of technology in modern times has a great influence in various aspects of life, including in the world of education. One example is the presence of ChatGPT among students in learning activities. The use of ChatGPT has many benefits but the use of this technology must still be addressed wisely to avoid ethical issues, copyright and plagiarism. This study aims to determine what factors influence the use of ChatGPT by students of the University of North Sumatra in education. By using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method with the variables used, namely the UTAUT2 model. The findings of this study state that 8 hypotheses of the relationship between variables tested in the study, of which 4 hypotheses of the relationship between variables are accepted and 4 hypotheses of the relationship between variables are rejected.